THE ACCOUNTING EXCHANGE. - Baily, H. H.; Kunze, H. L.; Littleton, A. C. (The Accounting Review, 1931)
The purpose of the elementary accounting courses given at the Chicago, Illinois-based University of Illinois is to give the students a thorough knowledge of basic transactions and fundamental procedure. Much of the material given in elementary accounting course can be disregarded when an examination is prepared because it represents routine work. Subjects such as, the classification of accounts, the preparation of short financial statements, adjusting entries, closing of the ledger, and books of original entry are included in the first-semester examination. The second-semester course is devoted more to accounting procedure and so for this reason the final examination given in the second semester may be counted upon to have a large number of difficult journal entries covering a wide variety of transactions. The examination for the second semester may include problems such as requiring adjusting entries, where the amount must be calculated as well as entries formulated, requiring the opening of the books of a corporation, or requiring the changing of a single proprietorship or partnership.